Analisis Stabilitas Lereng Terhadap Pembukaan Muara Sungai Akibat Pengaruh Sedimentasi di Pintu Air Tinggar Buntut - Lintang Fadhila Putri; Sekar Ayu Kuncaravita; Dayat Indri Yuliastuti (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Sedimentation in river channels may increase lateral earth pressure and reduce slope stability around hydraulic structures. However, studies concerning the effect of sediment accumulation on sheet pile-supported slopes at irrigation structures remain limited. This study evaluates the influence of sedimentation on slope stability at the Tinggar Buntut Water Gate, Kali Sadar River, using the Rankine method and the finite element method. Soil parameters were obtained from BBWS Brantas, while the sediment thickness of 1.5 m was estimated and validated by comparing riverbed elevations derived from Google Earth Pro historical imagery between 2019 and 2025. Soil behavior was simulated using the Mohr–Coulomb model under existing and sedimented conditions. The results show that active earth pressure increased from 74.93 kN/m to 126.62 kN/m, while the safety factor decreased from 1.44 to 0.85. Numerical analysis also indicated that the safety factor decreased from 1.7342 to 1.4420, accompanied by an increase in deformation from 3.40 × 10?³ m to 9.06 × 10?³ m.